Activation of the Canonical Wnt Signaling Pathway Induces Cementum Regeneration. (July 2015) - Han, Pingping; Ivanovski, Saso; Crawford, Ross; Xiao, Yin
ABSTRACT Canonical Wnt signaling is important in tooth development but it is unclear whether it can induce cementogenesis and promote the regeneration of periodontal tissues lost because of disease. Therefore, the aim of this study is to investigate the influence of canonical Wnt signaling enhancers on human periodontal ligament cell (hPDLCs) cementogenic differentiation in vitro and cementum repair in a rat periodontal defect model. Canonical Wnt signaling was induced by (1) local injection of lithium chloride; (2) local injection of sclerostin antibody; and (3) local injection of a lentiviral construct overexpressing β‐catenin. The results showed that the local activation of canonical Wnt signaling resulted in significant new cellular cementum deposition and the formation of well‐organized periodontal ligament fibers, which was absent in the control group. In vitro experiments using hPDLCs showed that the Wnt signaling pathway activators significantly increased mineralization, alkaline phosphatase (ALP) activity, and gene and protein expression of the bone and cementum markers osteocalcin (OCN), osteopontin (OPN), cementum protein 1 (CEMP1), and cementum attachment protein (CAP). Our results show that the activation of the canonical Wnt signaling pathway can induce in vivo cementum regeneration and in vitro cementogenic differentiation of hPDLCs. © 2014 American Society for Bone and Mineral Research © 2015 American Society for Bone and Mineral Research